KRITIK SOSIAL DALAM FILM “DI TIMUR MATAHARI” KARYA ARI SIHASALE SERTA IMPLEMENTASINYA TERHADAP PEMBELAJARAN SASTRA DI SMA NEGERI 3 KOTA TERNATE - Pipit Susanti; Pipit A. Susanti; Sartika Samad (CV. Multi Kreasi Media, 2022)
The main problem in this study is how the social criticism contained in the film In the East of the Sun by Ari Sihasale and its implications for the study of sastra in high school. Penelitian aims to interpretthesocial criticism contained in the film In the East of the Sun by Ari Sihasale and describe its implications for literature learning in high school. The research method is carried out by the literature method and the note-taking technique. In the data analysis method, qualitative descriptive methods are used. The results of this study found several social criticisms including (a) social criticism of educational problems (b) social criticism of the problem of poverty and (c) social criticism of inter-tribal wars. The results of this research are then used as literature teaching materials in high school. This teaching material is in accordance with basic competencies, namely finding values in short stories with a time allocation of 2 x 45 minutes. In addition to the short stories (based on the film In the East of the Sun) the teaching materials used by an audiovisual show are in the form of the film In the East of the Sun. The film contains a lot of life value and close educational value in everyday life.